2020
DOI: 10.3389/fendo.2020.585689
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Physical Activity on Bone Biomarkers in People With Osteoporosis: A Systematic Review

Abstract: Background: Bone imbalance between anabolic and catabolic processes at the level of remodeling unit due to the prevalence of resorbing activity, represents a health problem of aging. The consequence is the negative balance of bone turnover that can lead to osteoporosis. Physical activity (PA) can play a central role in the comprehensive management of osteoporosis, since it induces the anabolism of bone tissue. Bone turnover biomarkers, reflecting the cellular activity linked to bone metabolism, can represent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Clinically, ALP is often used to reflect bone metabolism activity and monitor drug response after treatment. 18,21,24,26 In our study, the 1 year ALP in Group 2 declined, which reflected a good response of the body to drugs to a certain extent. Compared to bone, the prostate is the primary source of ACP and PACP (the level of NACP is equal to ACP minus PACP).…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Clinically, ALP is often used to reflect bone metabolism activity and monitor drug response after treatment. 18,21,24,26 In our study, the 1 year ALP in Group 2 declined, which reflected a good response of the body to drugs to a certain extent. Compared to bone, the prostate is the primary source of ACP and PACP (the level of NACP is equal to ACP minus PACP).…”
Section: Discussionsupporting
confidence: 49%
“…Only approximately half of ALP in healthy adult blood comes from bone, which shows a lack of specificity. Clinically, ALP is often used to reflect bone metabolism activity and monitor drug response after treatment 18,21,24,26 . In our study, the 1 year ALP in Group 2 declined, which reflected a good response of the body to drugs to a certain extent.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…A systematic review of BTMs in subjects with osteoporosis revealed possible exercise benefits in terms of improving bone formation and decreasing bone resorption biomarkers ( 32 ). Whereas some studies have reported beneficial acute effects of exercise on BTMs ( 17 , 22 , 33 ), a direct comparison of heavy resistance training and aerobic running exercise has not yet been performed under strictly controlled conditions.…”
Section: Introductionmentioning
confidence: 99%
“…With advancing T age, alveolar elastic fibers degenerate, resulting in impaired gas exchange, respiratory muscle strength, and chest wall compliance indicates overall respiratory deterioration (5). A gradual reduction in bone density, osteoblastic activity and imbalance in bone formation and resorption deteriorates the body physical activity (6). As we get older, our lean body mass decreases while our body fat percentage rises and decline in body mass index, which are associated with ageing.…”
Section: Pathophysiology Of Ageingmentioning
confidence: 99%